2015
DOI: 10.1037/a0038036
|View full text |Cite
|
Sign up to set email alerts
|

How does a servant leader fuel the service fire? A multilevel model of servant leadership, individual self identity, group competition climate, and customer service performance.

Abstract: Building on a social identity framework, our cross-level process model explains how a manager's servant leadership affects frontline employees' service performance, measured as service quality, customer-focused citizenship behavior, and customer-oriented prosocial behavior. Among a sample of 238 hairstylists in 30 salons and 470 of their customers, we found that hair stylists' self-identity embedded in the group, namely, self-efficacy and group identification, partially mediated the positive effect of salon ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
262
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(280 citation statements)
references
References 56 publications
15
262
2
1
Order By: Relevance
“…Other findings reported that servant leadership enhanced self-efficacy [46,86], person-job fit [59], person-organisational fit [12], and leader-member exchange [22,75,79].…”
Section: Individual Outcomesmentioning
confidence: 96%
See 3 more Smart Citations
“…Other findings reported that servant leadership enhanced self-efficacy [46,86], person-job fit [59], person-organisational fit [12], and leader-member exchange [22,75,79].…”
Section: Individual Outcomesmentioning
confidence: 96%
“…The first study showed a direct positive relationship with group identification [86]. A second study reported that a serving culture mediated the relationship between servant leadership and employee identification [23].…”
Section: Team Outcomesmentioning
confidence: 97%
See 2 more Smart Citations
“…However, despite the aim of servant leaders to make an impact beyond the organization or its members, there is limited research supporting this assertion. Two notable exceptions demonstrate that servant leadership influences hair salon (Chen, Zhu, & Zhou, 2015) and restaurant customers , but to our knowledge no research exists exploring patients; patients differ from patrons of hair salons and restaurants in representing stakeholders who generally provide larger per person revenues to the organization and whose dissatisfaction may provide a greater risk in lawsuits or regulatory inquiries.…”
Section: Introductionmentioning
confidence: 99%